Muhammadiyah Dan Ideologi Islam Berkemajuan - Agustang, Andi Dody May Putra; Agustang, Andi; Jumadi, Jumadi (Universitas Negeri Makassar, 2022)
This study aims to determine the suitability of the perception of the Muhammadiyah community in the city of Makassar to the ideology of Progressive Islam. The subject of this study is the Muhammadiyah community in the city of Makassar. These include: (1) being involved or having been involved in the structure (management) of Muhammadiyah Makassar, (2) Ordinary citizens, namely those who have never been involved in the structure (management) of Muhammadiyah. This research selects informants purposively. By using descriptive qualitative analysis. The result showed that the internalization of progressive Islam by Muhammadiyah members was not uniform, but it gave rise to many perceptions. There are at least two categories of typology that the researchers found in relation to the concept of progressive Islam and the perception of the Muhammadiyah community in Makassar. The first is a